The role of context in understanding the use of tactical officers: A brief research note. (December 2021) - Jenkins, Bryce; Semple, Tori; Bennell, Craig; Huey, Laura
A small body of research suggests that the use of police tactical officers has become normalized in that they now commonly respond to "routine" calls rather than being restricted to high-risk situations. However, this research has tended to rely on crude data (i.e., call type), which fails to account for the context of the calls (e.g., the presence of potential risk factors that might warrant tactical resources). In this brief research note, we sought to expand upon previous literature by examining the risk factors associated with tactical calls in a Canadian police service. We found that various risk factors were present in many of the calls that tactical officers responded to, some of which might be classified as "routine" (suicide threats, well-being checks, domestic disturbances, etc.). The presence of such risk factors highlights the need to consider context when attempting to understand the use (and consequences) of tactical officers. More rigorous tracking of these factors by police services will facilitate such research and inform policies around the use of tactical resources.